2006
DOI: 10.1007/bf02706504
|View full text |Cite
|
Sign up to set email alerts
|

Surface characterization of sol-gel derived indium tin oxide films on glass

Abstract: Indium tin oxide (ITO) films containing different In : Sn atomic ratios, viz. 90 : 10, 70 : 30, 50 : 50, 30 : 70, were deposited on two types of glass substrates by sol-gel spinning technique. XPS analysis of the films was done under as-received and after-sputtering conditions. The narrow spectra obtained for the Na1s, In3d, Sn3d and O1s have been discussed. Oxygen was found to exist in three chemical environments in as-received samples due to the existence of (i) environmental hydroxyl (-OH) group, (ii) cryst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(33 citation statements)
references
References 28 publications
4
29
0
Order By: Relevance
“…X-ray Diffraction (XRD) Figure 1 depicts the X-ray diffraction (XRD) patterns of (a) FTO substrate, (b-c) In 2 S 3 films grown on FTO substrate by 10hr (H 10 -In 2 S 3 ) and 24hr hydrothermal reactions (H 24 -In 2 S 3 ), Figure 1d is for the In 2 S 3 film grown on FTO substrate by the sulfurization method (S-In 2 S 3 ). All the three XRD patterns (H 10 -In 2 S 3 , H 24 To study the formation and transformation of In(OH) 3 , hydrothermal reactions for different durations (2, 7, 10, 16 and 24 h) were carried out. After 2h reaction, completely white film of In(OH) 3 is obtained (please see the supporting information, Figure SI-1a).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…X-ray Diffraction (XRD) Figure 1 depicts the X-ray diffraction (XRD) patterns of (a) FTO substrate, (b-c) In 2 S 3 films grown on FTO substrate by 10hr (H 10 -In 2 S 3 ) and 24hr hydrothermal reactions (H 24 -In 2 S 3 ), Figure 1d is for the In 2 S 3 film grown on FTO substrate by the sulfurization method (S-In 2 S 3 ). All the three XRD patterns (H 10 -In 2 S 3 , H 24 To study the formation and transformation of In(OH) 3 , hydrothermal reactions for different durations (2, 7, 10, 16 and 24 h) were carried out. After 2h reaction, completely white film of In(OH) 3 is obtained (please see the supporting information, Figure SI-1a).…”
Section: Resultsmentioning
confidence: 99%
“…Indium interstitials or quasi-interstitials). Biswas et al 24 have also noted such a contribution in their sol-gel derived films and this contribution was seen to vanish after surface cleaning by sputtering. This made the authors assign this contribution to free surface hydroxyl groups.…”
Section: X-ray Photoelectron Spectroscopy (Xps)mentioning
confidence: 88%
“…Meanwhile, according to Fig. 5B, the Sn 3d (3d 5/2 and 3d 3/2 ) doublet peaks have a very strong signal prior to the electrodeposition of Au at $486/$496 eV [41]. After backfilling, these peaks significantly decreased, which vividly suggests that the cavities in the inverse opaline film array were almost covered.…”
Section: Polycarbazole-au Co-patternsmentioning
confidence: 87%
“…A glance of the spectra showed that they were different and the best fitting presented three components at binding energies of 530.5 ± 0.1 (peak A), 531.5 ± 0.1 (peak B), and 532.3 ± 0.1 eV (peak C). Similar to other recent studies on ITO surfaces, we assigned peak A, peak B, and peak C to lattice oxygen in a crystalline ITO phase [20,21], in oxygen deficient regions of the In 2 O 3 matrix [20,22], and in hydroxyl groups on the ITO surface [21, 23]. The binding energy and relative peak area of each component were summarized in Table 3.…”
Section: Methodsmentioning
confidence: 96%